Composite positive electrode material, preparation method thereof and sodium ion battery
MXene nanosheets were prepared by acid etching method in the positive electrode material of sodium ion battery, and NamCu1-x-y-zNixFeyMnzO2 positive electrode material was grown in situ on its surface and precious metals Ag nanoparticles and AgCl were introduced, which solved the problem of low comprehensive performance of sodium ion battery and significantly improved the conductivity and cyclic stability.
Patent Information
- Application Number
- CN202411899891.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing sodium ion batteries have low comprehensive performance, poor structural stability, low conductivity, difficult to control the product morphology, and electrolyte erosion leads to rapid attenuation of the capacity of the positive electrode material and severe polarization.
MXene nanosheets were prepared by acid etching assisted in step-by-step sonication treatment. NamCu1-x-y-zNixFeyMnzO2 positive electrode material was grown in situ on the surface of MXene nanosheets by impregnation-precipitation, and noble metal Ag nanoparticles and AgCl were introduced by impregnation-photoreduction method to optimize the layer spacing and increase the active site.
The conductivity and structural stability of the composite positive electrode material are improved, the charge and discharge rate and cycle stability are optimized, the contact between the electrolyte and the positive electrode material is reduced, and the capacity attenuation problem is suppressed.
Smart Images

Figure CN119695120A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials for sodium ion batteries, and in particular to a composite positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] At present, lithium-ion batteries are widely used in mobile electronic devices, computers, electric vehicles, communications, energy storage and other fields. However, due to the scarce reserves and uneven distribution of lithium resources, it is difficult to meet the rapidly growing application needs, which has severely restricted its large-scale development. Sodium and lithium are in the same main group, with similar physical and chemical properties. Sodium is the sixth most abundant element in the world and is widely distributed. Therefore, sodium-ion batteries are considered to be the next generation of energy storage systems that can replace lithium-ion batteries. In sodium-ion batteries, the positive electrode material is an important component, which plays a key role in providing sodium ions and determining the energy density of the battery. Among them, layered transition metal oxides are considered to be the most competitive and commercially promising sodium-ion battery positive electrode materials that are expected to be the first to be industrialized because of their rich variety, high discharge voltage, high energy density and easy synthesis.
[0003] Among the layered oxides of sodium ion batteries, the sodium salt of the quaternary material copper-nickel-iron-manganese has the advantages of abundant raw materials, low price, good cycle performance, and moderate specific capacity, but there are still some defects, such as poor structural stability, poor conductivity, and difficult to control the morphology of the product, and the electrolyte will also corrode the positive electrode material, which ultimately leads to rapid attenuation of the positive electrode material capacity, severe polarization, and poor cycle stability. It can be seen that the performance of the single-component sodium ion battery positive electrode material will be limited by the characteristics of the material itself, thereby hindering its practical application. Therefore, it is necessary to perform surface modification on it, including ion doping, conductive material composite or precious metal deposition, etc. The existing patent publication number CN115548337A discloses a surface-modified battery material, its preparation method and battery, which is heated to a high temperature The battery material is mixed and reacted with a salt solution (including inorganic salts and organic salts) to change the surface structure of the battery material, and realize surface doping, defect manufacturing and / or functional group grafting. Although the battery material using the salt solution quenching method has higher specific capacity, higher first-cycle coulombic efficiency and capacity retention rate compared with the unmodified material, the increase in charge and discharge rate is limited, resulting in low overall performance of the battery. Summary of the invention
[0004] The main purpose of the present invention is to provide a composite positive electrode material and a preparation method thereof and a sodium ion battery, aiming to solve the technical problem that the comprehensive performance of existing sodium ion batteries is not high.
[0005] To achieve the above object, the present invention provides a method for preparing a composite positive electrode material, the method comprising the following steps:
[0006] Step 1, adding a preset mass of lithium fluoride into a concentrated hydrochloric acid solution to completely dissolve it, and slowly adding a MXene precursor and stirring it for a preset time to obtain a colloidal suspension solution;
[0007] Step 2, washing the colloidal suspension solution by centrifugation with anhydrous ethanol, and detecting the pH value of the supernatant until the pH value reaches 5 to 10, and then performing step-by-step ultrasonic treatment and vacuum freeze drying to obtain MXene nanosheet powder;
[0008] Step 3: Place the MXene nanosheet powder in a silver nitrate aqueous solution and soak it in a dark environment for 2 to 12 hours to allow the Ag + The Ag is fully adsorbed on the MXene nanosheets and then irradiated with UV light for a preset time to make the Ag + In situ Ag generation 0 After irradiation, the Ag / MXene nanocomposite material was obtained by centrifugal washing and separation with anhydrous ethanol and vacuum freeze drying.
[0009] Step 4: weigh a preset mass of copper source, nickel source, iron source and manganese source, immerse them in a sodium chloride solution, and add the Ag / MXene nanocomposite prepared in step 3, and continue to immerse them in a dark environment for 2 to 12 hours to generate sodium ion quaternary cathode material in situ on the MXene nanosheets and successfully deposit AgCl nanoparticles, and then irradiate with ultraviolet light for a preset time to make the remaining Ag + In situ Ag generation 0 After irradiation, the Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / MXene metal nanocomposite positive electrode material, wherein 0.5≤m≤1.5, 0 <x<0.5,0<y<0.5,0<z<1,0<1-x-y-z<1。
[0010] Optionally, in step 1, the mass volume ratio of lithium fluoride to concentrated hydrochloric acid solution is (1-5) g: (15-100) mL, and the mass fraction of the concentrated hydrochloric acid solution is 34%.
[0011] Optionally, in step 2, the MXene nanosheets include Ti3C2T x 、Nb2CT x 、Mo2CT x 、V2CT x 、Ti2CT x 、Ti2NT x 、V4C3T x 、Nb4C3Tx 、Ti3CNT x 、Ta4C3T x and TiNbCT x At least one of .
[0012] Optionally, in step 2, the time of the stepwise ultrasonication is 10 to 120 min.
[0013] Optionally, in step 3, the concentration of the silver nitrate aqueous solution is 0.1 mol / L, and the mass volume ratio of the MXene nanosheet powder to the silver nitrate aqueous solution is (10-500) mg: (10-50) mL.
[0014] Optionally, in step 4, the copper source includes at least one of copper sulfate, copper chloride, copper nitrate and copper acetate, the nickel source includes at least one of nickel sulfate, nickel chloride, nickel nitrate and nickel acetate, the iron source includes at least one of ferric sulfate and / or ferrous sulfate, ferric chloride and / or ferrous chloride, ferric nitrate and / or ferrous nitrate, ferric citrate and ferric acetate, and the manganese source includes at least one of manganese sulfate, manganese chloride, manganese nitrate and manganese acetate.
[0015] Optionally, in step 4, the corresponding metal molar ratios of the copper source, nickel source, iron source and manganese source are (0-1):(0-0.5):(0-0.5):(0-1).
[0016] Optionally, the UV light irradiation time in step 3 and step 4 is 60 minutes respectively.
[0017] In addition, in order to achieve the above-mentioned purpose, the present invention also provides a composite positive electrode material, wherein the composite positive electrode material is prepared according to any one of the above-mentioned methods for preparing the sodium ion positive electrode material.
[0018] In addition, in order to achieve the above purpose, a sodium ion battery is provided, which includes a positive electrode sheet. The positive electrode sheet is prepared by adding the above composite positive electrode material, a conductive agent and a binder PVDF in a mass ratio of 8:1:1 to an NMP solution and stirring and mixing the mixture, then uniformly coating the mixture on an aluminum foil, and finally baking the mixture in a vacuum drying oven at 70 to 100°C.
[0019] Beneficial effects:
[0020] (1) MXene nanosheets were prepared by acid etching assisted by step-by-step ultrasonic treatment. They have ultra-thin layered structures and unique large specific surface areas, which can be used to improve the dispersion and uniformity of composite cathode materials. m Cu 1-x-y-z Ni x Fe y Mn zThe O2 cathode material is in situ grown on the surface of the MXene nanosheets, and the precious metal Ag nanoparticles and AgCl introduced by the impregnation-photoreduction method increase the conductivity and active sites of the composite material. The optimized interlayer spacing and increased active sites make the composite material have a faster charge and discharge rate. The step-by-step ultrasonic treatment improves the interlayer spacing of the two-dimensional MXene nanosheets, avoids the interlayer collapse problem, and increases the interlayer energy storage space.
[0021] (2) Based on the excellent mechanical properties and high conductivity of the prepared two-dimensional material MXene nanosheets, it can not only be used as a carrier to support the positive electrode material of sodium ion batteries, but also improve the conductivity of the composite material and promote Na + The transmission of the two-dimensional material MXene nanosheets has high chemical stability and thermal stability, which can form a protective barrier to prevent the contact between the electrolyte and the positive electrode material. Reduce the side reactions between the positive electrode material and the electrolyte. This effectively suppresses the problem of rapid capacity decay during the battery cycle.
[0022] (3) The entire preparation process is simple and controllable, easy to operate, does not require special instruments and experimental conditions, is low in cost, consumes little energy, and is green and feasible.
[0023] (4) The loaded precious metal Ag nanoparticles and their derivatives AgCl and MXene nanosheets work together and complement each other, which improves the overall structural stability of the composite material, significantly improves the discharge capacity and cycle stability of the composite material, and has excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a composite positive electrode material for a sodium ion battery in the present invention.
[0025] Figure 2 for Figure 1 Flow chart of the preparation of MXene nanosheet powder;
[0026] Figure 3 The single layer Ti3C2T is obtained after etching the aluminum atoms in the precursor Ti3AlC2 and ultrasonicating in Example 1 of the present invention. X Scanning electron microscopy image of the nanosheets.
[0027] Figure 4 The single layer Ti3C2T is obtained after etching the aluminum atoms in the precursor Ti3AlC2 and ultrasonicating in Example 1 of the present invention. X Atomic force microscopy image of the nanosheet.
[0028] Figure 5 is Na in Example 6 of the present invention m Cu1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X Scanning electron microscope image of the composite positive electrode material for sodium ion batteries at 5000 times magnification.
[0029] Figure 6 is Na in Example 7 of the present invention m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X Scanning electron microscope image of the composite positive electrode material for sodium ion batteries at 10,000 times magnification.
[0030] Figure 7 is Na in Example 7 of the present invention m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X X-ray diffraction pattern of composite positive electrode material for sodium ion battery.
[0031] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0032] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0033] See also Figure 1-2 The present invention provides a schematic flow chart of a method for preparing a composite positive electrode material, wherein the method comprises the following steps:
[0034] Step 1, add a preset mass of lithium fluoride to a concentrated hydrochloric acid solution and dissolve it completely, slowly add a MXene precursor and stir it for a preset time, use hydrochloric acid and lithium fluoride as etchants to etch the MXene precursor to obtain a colloidal suspension solution. Wherein, the mass volume ratio of lithium fluoride to concentrated hydrochloric acid solution is (1-5) g: (15-100) mL, preferably 1 g: 15 mL, the mass fraction of the concentrated hydrochloric acid solution is 34%, and the concentration is 9 mol / L. Preferably, the MXene precursor includes at least one of Ti3AlC2, Nb2AlC, Mo2AlC, V2AlC, Ti2AlC, Ti2AlN, V4AlC3, Nb4AlC3, Ti3AlCN, Ta4AlC3 and TiNbAlC, and the MXene nanosheets after the etching reaction include Ti3C2Tx 、Nb2CT x 、Mo2CT x 、V2CT x 、Ti2CT x 、Ti2NT x 、V4C3T x 、Nb4C3T x 、Ti3CNT x 、Ta4C3T x and TiNbCT x At least one of them shows that MXene nanosheets are obtained by acid leaching to remove aluminum through etching reaction, followed by centrifugal washing and ultrasonic peeling.
[0035] Step 2, the colloidal suspension solution is centrifuged and washed with anhydrous ethanol, and the pH value of the supernatant is detected until the pH value reaches 5 to 10, and then step-by-step ultrasonic treatment and vacuum freeze drying are performed to obtain MXene nanosheet powder. Anhydrous ethanol is centrifuged and washed multiple times, and the pH value of the supernatant after washing is detected in real time. Preferably, the pH value can be but is not limited to 5, 6, 7, 8, 9, 10. The time for the step-by-step ultrasonic treatment is 10 to 120 minutes. The initial purpose of ultrasound is to improve the interlayer spacing of the MXene material and avoid interlayer collapse. And the thickness of the MXene nanosheet finally obtained is nanometer level, specifically 1-2nm, and it is a single-layer sheet structure with a high yield.
[0036] Step 3: Place the MXene nanosheet powder in a silver nitrate aqueous solution and soak it in a dark environment for 2 to 12 hours to allow the Ag + The Ag is fully adsorbed on the MXene nanosheets and then irradiated with UV light for a preset time to make the Ag + In situ Ag generation 0 , after irradiation, centrifugal washing and separation with anhydrous ethanol and vacuum freeze drying are used to obtain Ag / MXene nanocomposite materials. Among them, the single substance Ag in the Ag / MXene nanocomposite material is deposited on the MXene nanosheets to increase the conductivity and active sites of the composite material, that is, this step is to deposit metal Ag nanoparticles in situ on the pretreated MXene nanosheets by the impregnation-photoreduction method, and the noble metal Ag nanoparticles and AgCl introduced by the impregnation-photoreduction method increase the conductivity and active sites of the composite material. The optimized interlayer spacing and increased active sites make the composite material have a faster charge and discharge rate; the ultraviolet light irradiation time is 60min, the concentration of the silver nitrate aqueous solution is 0.1mol / L, and the mass volume ratio of the MXene nanosheet powder to the silver nitrate aqueous solution is (10-500)mg:(10-50)mL, preferably 1mg:1mL.
[0037] Step 4: Weigh a preset mass of copper source, nickel source, iron source and manganese source, immerse them in sodium chloride solution, and add the Ag / MXene nanocomposite prepared in Step 3. Keep soaking in the dark environment for 2 - 12 h to in-situ generate a sodium-ion quaternary cathode material on the MXene nanosheets and successfully deposit AgCl nanoparticles. Then irradiate with an ultraviolet lamp for a preset time to convert the remaining Ag + to in-situ generate Ag 0 . After irradiation, perform centrifugal washing and separation with absolute ethanol and vacuum freeze-drying treatment to obtain Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / MXene metal nanocomposite cathode material, where 0.5 ≤ m ≤ 1.5, 0 < x < 0.5, 0 < y < 0.5, 0 < z < 1, 0 < 1 - x - y - z < 1, and the sum of the number of copper, nickel, iron, and manganese atoms in the general formula of the metal nanocomposite cathode material is 1. The copper source, nickel source, iron source, and manganese source are all corresponding metal salts. Preferably, the copper source includes at least one of copper sulfate, copper chloride, copper nitrate, and copper acetate; the nickel source includes at least one of nickel sulfate, nickel chloride, nickel nitrate, and nickel acetate; the iron source includes at least one of ferric sulfate and / or ferrous sulfate, ferric chloride and / or ferrous chloride, ferric nitrate and / or ferrous nitrate, ferric citrate, and ferric acetate; the manganese source includes at least one of manganese sulfate, manganese chloride, manganese nitrate, and manganese acetate. The noble metal Ag nanoparticles and their derivative AgCl and the MXene nanosheets in this step cooperate with each other and complement each other's advantages, improving the overall structural stability of the composite material, significantly enhancing the discharge specific capacity and cycle stability of the composite material, and showing excellent electrochemical performance.
[0038] Further, in Step 4, the corresponding metal molar ratio of the copper source, nickel source, iron source, and manganese source is (0 - 1):(0 - 0.5):(0 - 0.5):(0 - 1).
[0039] Further, the irradiation time of the ultraviolet lamp in Step 4 is 60 min.
[0040] Further, the soaking time in Steps 3 and 4 can be, but is not limited to, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h.
[0041] Furthermore, the composite positive electrode material, the conductive agent and the binder PVDF are added to the NMP solution in a mass ratio of 8:1:1 and fully stirred and mixed, and then evenly coated on an aluminum foil, and finally baked in a vacuum drying oven at 70-100°C to obtain a positive electrode sheet, and the positive electrode sheet is paired with a metallic sodium negative electrode and assembled into a CR2032 button battery in a glove box filled with an inert atmosphere.
[0042] The present invention is based on a single Na m Cu 1-x-y-z Ni x Fe y Mn z O2 quaternary cathode materials have low rate performance, poor stability and conductivity, and are very easy to react with the electrolyte, resulting in reduced capacity and poor cycle performance. MXene nanosheets and precious metal Ag nanoparticles are used to modify their surface. MXene nanosheets have stable chemical properties, good thermal stability and mechanical properties, high conductivity and large specific surface area. They can also be used as a good carrier to support sodium ion battery cathode materials, improve the conductivity of cathode materials and promote Na + It can not only transmit, but also form a protective barrier for the positive electrode material, reduce the continuous erosion of the electrolyte on the positive electrode material, and inhibit the capacity decay problem of the battery during the cycle. The precious metal Ag nanoparticles and its derivative AgCl can increase the conductivity and active sites of the positive electrode material, thereby making the quaternary / MXene metal nanocomposite material have a faster charge and discharge rate and excellent electrochemical performance.
[0043] Furthermore, in order to better illustrate the preparation process of the composite positive electrode material in the present invention, the following is a detailed description through specific examples.
[0044] Example 1
[0045] This embodiment provides a novel quaternary Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X The preparation method of metal nanocomposite positive electrode material and sodium ion battery comprises the following steps:
[0046] (1) Prepare a concentrated hydrochloric acid solution of a certain concentration, add lithium fluoride to the above hydrochloric acid solution and stir for 10-20 minutes until the lithium fluoride is completely dissolved, then slowly add Ti3AlC2 to the solution to prevent violent reaction, and continue stirring for a certain period of time after the addition is completed. After the etching reaction is completed, the obtained colloidal suspension solution is centrifuged and washed several times with anhydrous ethanol, and the pH of the supernatant is tested until the pH value of the supernatant reaches 6. Then ultrasonically treat for 60 minutes to make it evenly dispersed, and Ti3C2T X Nanosheet ethanol solution, and finally Ti3C2T X Ti3C2T nanosheets can be obtained by vacuum freeze drying of ethanol solution X Nanosheet powder, for observation of Ti3C2T X- The microscopic morphology of MXene nanosheets was obtained by scanning electron microscopy and atomic force microscopy after dilution and air drying of the colloidal solution. Figure 3-4 The scanning electron microscope and atomic force microscope images shown in the figure show that Ti3C2T X- MXene shows a single-layer lamellar structure, with each layer separated from each other and dispersed relatively evenly.
[0047] (2) Ti3C2T X After weighing the nanosheet powder, soak it in a beaker containing silver nitrate aqueous solution, seal it with laboratory sealing film and let it stand directly to promote the adsorption of silver ions. This process is carried out in a dark environment. Soak for 2 hours to allow Ag + Fully adsorbed on Ti3C2T X The solution in the beaker was then irradiated with a laboratory UV lamp for 60 minutes to reduce the Ag + In situ Ag generation 0 , Ag 0 Successfully in-situ deposited on Ti3C2T X On nanosheets.
[0048] (3) According to the stoichiometric ratio of each element in the quaternary material, copper acetate, nickel acetate, ferrous chloride and manganese acetate were weighed and immersed in a sodium chloride solution for in-situ oxidation. X The nanocomposite material was added and immersed for 3 h to form a X The sodium ion quaternary cathode material was generated in situ on the nanosheet and AgCl nanoparticles were successfully deposited. The nanosheet was sealed with a laboratory sealing film and left to stand directly. This process also needs to be operated in a dark environment throughout the process. m Cu 1-x-y-z Ni x Fe y Mn z O2 on Ti3C2TX The nanosheets were fully reacted and the solution was exposed to ultraviolet light for 60 minutes to remove some of the residual Ag. + Reduction to elemental Ag 0 Then use anhydrous ethanol to centrifuge and wash to separate. Finally, vacuum freeze-dry to obtain Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X Metal nanocomposite cathode materials.
[0049] (4) The Na synthesized above m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X The metal nanocomposite positive electrode material, the conductive agent and the binder PVDF were added to the NMP solution in a mass ratio of 8:1:1, and stirred and mixed thoroughly to obtain a uniform slurry. The slurry was then evenly coated on an aluminum foil and placed in a vacuum drying oven and baked at 70°C to obtain a positive electrode sheet.
[0050] (5) Pair the positive electrode sheet in step (4) with the metallic sodium negative electrode, assemble them into a CR2032 button cell in a glove box filled with an inert atmosphere, and test the electrochemical properties of the composite positive electrode material.
[0051] Example 2
[0052] This embodiment provides a novel quaternary Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Nb2CT X The preparation method of metal nanocomposite positive electrode material and sodium ion battery comprises the following steps:
[0053] (1) Prepare a concentrated hydrochloric acid solution of a certain concentration, add lithium fluoride to the above hydrochloric acid solution and stir for 10-20 minutes until the lithium fluoride is completely dissolved, then slowly add Nb2AlC to the solution to prevent violent reaction, and continue stirring for a certain period of time after the addition is completed. After the etching reaction is completed, the obtained colloidal suspension solution is centrifuged and washed several times with anhydrous ethanol, and the pH of the supernatant is tested until the pH value of the supernatant reaches 5. Then ultrasonically treat it for 60 minutes to make it evenly dispersed, and Nb2CT is obtained. X Nanosheet ethanol solution, and finally Nb2CT XNb2CT can be obtained by vacuum freeze drying of nanoethanol solution X Nanosheet powder.
[0054] (2) Nb2CT X After weighing the nanosheet powder, soak it in a beaker containing silver nitrate aqueous solution, seal it with laboratory sealing film and let it stand directly to promote the adsorption of silver ions. This process is carried out in a dark environment. Soak for 4 hours to allow Ag + Fully adsorbed on Nb2CT X The solution in the beaker was then irradiated with a laboratory UV lamp for 60 minutes to reduce the Ag + In situ Ag generation 0 , Ag 0 Successfully in-situ deposited on Nb2CT X On nanosheets;
[0055] (3) According to the stoichiometric ratio of each element in the quaternary material, copper acetate, nickel acetate, ferrous chloride and manganese acetate were weighed and immersed in a sodium chloride solution for in-situ oxidation. X The nanocomposite material was added and immersed for 5 h to form Nb2CT X The sodium ion quaternary cathode material was generated in situ on the nanosheet and AgCl nanoparticles were successfully deposited. The nanosheet was sealed with a laboratory sealing film and left to stand directly. This process also needs to be operated in a dark environment throughout the process. m Cu 1-x-y-z Ni x Fe y Mn z O2 in Nb2CT X The nanosheets were fully reacted and the solution was exposed to ultraviolet light for 60 minutes to remove some of the residual Ag. + Reduction to elemental Ag 0 Then use anhydrous ethanol to centrifuge and wash to separate. Finally, vacuum freeze-dry to obtain Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Nb2CT X Metal nanocomposite cathode materials.
[0056] (4) The Na synthesized above m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Nb2CT XThe metal nanocomposite positive electrode material, the conductive agent and the binder PVDF were added to the NMP solution in a mass ratio of 8:1:1, and stirred and mixed thoroughly to obtain a uniform slurry. The slurry was then evenly coated on an aluminum foil and placed in a vacuum drying oven and baked at 70°C to obtain a positive electrode sheet.
[0057] (5) Pair the positive electrode sheet in step (4) with the metallic sodium negative electrode, assemble them into a CR2032 button cell in a glove box filled with an inert atmosphere, and test the electrochemical properties of the composite positive electrode material.
[0058] Example 3
[0059] This embodiment provides a novel quaternary Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ta4C3T X The preparation method of metal nanocomposite positive electrode material and sodium ion battery comprises the following steps:
[0060] (1) Prepare a concentrated hydrochloric acid solution of a certain concentration, add lithium fluoride to the hydrochloric acid solution and stir for 10-20 minutes until the lithium fluoride is completely dissolved, then slowly add Ta4Al C3 to the solution to prevent violent reaction, and continue stirring for a certain period of time after the addition is completed. After the etching reaction is completed, the obtained colloidal suspension solution is centrifuged and washed several times with anhydrous ethanol, and the pH of the supernatant is tested until the pH value of the supernatant reaches 7. Then ultrasonically treat for 60 minutes to make it evenly dispersed, and Ta4C3T3O4 is obtained. X Nanosheet ethanol solution, and finally Ta4C3T X Ta4C3T can be obtained by vacuum freeze drying of nano-ethanol solution X Nanosheet powder.
[0061] (2) Ta4C3T X After weighing the nanosheet powder, soak it in a beaker containing silver nitrate aqueous solution, seal it with laboratory sealing film and let it stand directly to promote the adsorption of silver ions. This process is carried out in a dark environment. Soak for 6 hours to allow Ag to + Fully adsorbed on Ta4C3T X The solution in the beaker was then irradiated with a laboratory UV lamp for 60 minutes to reduce the Ag + In situ Ag generation 0 , Ag 0 Successfully in-situ deposited on Ta4C3T X On nanosheets;
[0062] (3) According to the stoichiometric ratio of each element in the quaternary material, copper acetate, nickel acetate, ferrous chloride and manganese acetate were weighed and immersed in a sodium chloride solution for in-situ oxidation. X The nanocomposite material was added and immersed for 7 hours to form Ta4C3T X The sodium ion quaternary cathode material was generated in situ on the nanosheet and AgCl nanoparticles were successfully deposited. The nanosheet was sealed with a laboratory sealing film and left to stand directly. This process also needs to be operated in a dark environment throughout the process. m Cu 1-x-y-z Ni x Fe y Mn z O2 on Ta4C3T X The nanosheets were fully reacted and the solution was exposed to ultraviolet light for 60 minutes to remove some of the residual Ag. + Reduction to elemental Ag 0 Then use anhydrous ethanol to centrifuge and wash to separate. Finally, vacuum freeze-dry to obtain Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ta4C3T X Metal nanocomposite cathode materials.
[0063] (4) The Na synthesized above m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ta4C3T X The metal nanocomposite positive electrode material, the conductive agent and the binder PVDF were added to the NMP solution in a mass ratio of 8:1:1, and stirred and mixed thoroughly to obtain a uniform slurry. The slurry was then evenly coated on an aluminum foil and placed in a vacuum drying oven and baked at 80°C to obtain a positive electrode sheet.
[0064] (5) Pair the positive electrode sheet in step (4) with the metallic sodium negative electrode, assemble them into a CR2032 button cell in a glove box filled with an inert atmosphere, and test the electrochemical properties of the composite positive electrode material.
[0065] Example 4
[0066] This embodiment provides a novel quaternary Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / V4C3TX The preparation method of metal nanocomposite positive electrode material and sodium ion battery comprises the following steps:
[0067] (1) Prepare a concentrated hydrochloric acid solution of a certain concentration, add lithium fluoride to the above hydrochloric acid solution and stir for 10-20 minutes until the lithium fluoride is completely dissolved, then slowly add V4Al C3 to the solution to prevent violent reaction, and continue stirring for a certain period of time after the addition is completed. After the etching reaction is completed, the obtained colloidal suspension solution is centrifuged and washed several times with anhydrous ethanol, and the pH of the supernatant is tested until the pH value of the supernatant reaches 8. Then ultrasonically treat it for 60 minutes to make it evenly dispersed, and V4C3T is obtained. X Nanosheet ethanol solution, and finally V4C3T X V4C3T can be obtained by vacuum freeze drying of nanoethanol solution X Nanosheet powder.
[0068] (2) V4C3T X After weighing the nanosheet powder, soak it in a beaker containing silver nitrate aqueous solution, seal it with laboratory sealing film and let it stand directly to promote the adsorption of silver ions. This process is carried out in a dark environment. Soak for 8 hours to allow Ag to + Fully adsorbed on V4C3T X The solution in the beaker was then irradiated with a laboratory UV lamp for 60 minutes to reduce the Ag + In situ Ag generation 0 , Ag 0 Successful in-situ deposition on V4C3T X On nanosheets;
[0069] (3) According to the stoichiometric ratio of each element in the quaternary material, copper acetate, nickel acetate, ferrous chloride and manganese acetate were weighed and immersed in a sodium chloride solution for in-situ oxidation. X The nanocomposite material was added and immersed for 9 hours to form a V4C3T X The sodium ion quaternary cathode material was generated in situ on the nanosheet and AgCl nanoparticles were successfully deposited. The nanosheet was sealed with a laboratory sealing film and left to stand directly. This process also needs to be operated in a dark environment throughout the process. m Cu 1-x-y-z Ni x Fe y Mn z O2 on V4C3T X The nanosheets were fully reacted and the solution was exposed to ultraviolet light for 60 minutes to remove some of the residual Ag. + Reduction to elemental Ag 0Then use anhydrous ethanol to centrifuge and wash to separate. Finally, vacuum freeze-dry to obtain Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / V4C3T X Metal nanocomposite cathode materials.
[0070] (4) The Na synthesized above m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / V4C3T X The metal nanocomposite positive electrode material, the conductive agent and the binder PVDF were added to the NMP solution in a mass ratio of 8:1:1, and stirred and mixed thoroughly to obtain a uniform slurry. The slurry was then evenly coated on an aluminum foil and placed in a vacuum drying oven and baked at 80°C to obtain a positive electrode sheet.
[0071] (5) Pair the positive electrode sheet in step (4) with the metallic sodium negative electrode, assemble them into a CR2032 button cell in a glove box filled with an inert atmosphere, and test the electrochemical properties of the composite positive electrode material.
[0072] Example 5
[0073] This embodiment provides a novel quaternary Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X The preparation method of metal nanocomposite positive electrode material and sodium ion battery comprises the following steps:
[0074] (1) Prepare a concentrated hydrochloric acid solution of a certain concentration, add lithium fluoride to the above hydrochloric acid solution and stir for 10-20 minutes until the lithium fluoride is completely dissolved, then slowly add Ti3AlC2 to the solution to prevent violent reaction, and continue stirring for a certain period of time after the addition is completed. After the etching reaction is completed, the obtained colloidal suspension solution is centrifuged and washed several times with anhydrous ethanol, and the pH of the supernatant is tested until the pH value of the supernatant reaches 9. Then ultrasonically treat it for 10 minutes to make it evenly dispersed, and Ti3C2T X Single-layer nanosheet ethanol solution, finally Ti3C2T X Ti3C2T can be obtained by vacuum freeze drying of nanoethanol solution X Nanosheet powder.
[0075] (2) Ti3C2TX After weighing the nanosheet powder, soak it in a beaker containing silver nitrate aqueous solution, seal it with laboratory sealing film and let it stand directly to promote the adsorption of silver ions. This process is carried out in a dark environment. Soak for 10 hours to allow Ag to + Fully adsorbed on Ti3C2T X The solution in the beaker was then irradiated with a laboratory UV lamp for 60 minutes to reduce the Ag + In situ Ag generation 0 , Ag 0 Successfully in-situ deposited on Ti3C2T X On nanosheets;
[0076] (3) According to the stoichiometric ratio of each element in the quaternary material, copper acetate, nickel acetate, ferrous chloride and manganese acetate were weighed and immersed in a sodium chloride solution for in-situ oxidation. X The nanocomposite materials were added and immersed for 11 hours to form a X The sodium ion quaternary cathode material was generated in situ on the nanosheet and AgCl nanoparticles were successfully deposited. The nanosheet was sealed with a laboratory sealing film and left to stand directly. This process also needs to be operated in a dark environment throughout the process. m Cu 1-x-y-z Ni x Fe y Mn z O2 on Ti3C2T X The nanosheets were fully reacted and the solution was exposed to ultraviolet light for 60 minutes to remove some of the residual Ag. + Reduction to elemental Ag 0 Then use anhydrous ethanol to centrifuge and wash to separate. Finally, vacuum freeze-dry to obtain Na m Cu 1-x-y-z Ni x Fe y Mn z O2Ag@AgCl / Ti3C2T X Metal nanocomposite cathode materials.
[0077] (4) The Na synthesized above m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T XThe metal nanocomposite positive electrode material, the conductive agent and the binder PVDF were added to the NMP solution in a mass ratio of 8:1:1, and stirred and mixed thoroughly to obtain a uniform slurry. The slurry was then evenly coated on an aluminum foil and placed in a vacuum drying oven and baked at 90°C to obtain a positive electrode sheet.
[0078] (5) Pair the positive electrode sheet in step (4) with the metallic sodium negative electrode, assemble them into a CR2032 button cell in a glove box filled with an inert atmosphere, and test the electrochemical properties of the composite positive electrode material.
[0079] Example 6
[0080] This embodiment provides a novel quaternary Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X The preparation method of metal nanocomposite positive electrode material and sodium ion battery comprises the following steps:
[0081] (1) Prepare a concentrated hydrochloric acid solution of a certain concentration, add lithium fluoride to the above hydrochloric acid solution and stir for 10-20 minutes until the lithium fluoride is completely dissolved, then slowly add Ti3AlC2 to the solution to prevent violent reaction, and continue stirring for a certain period of time after the addition is completed. After the etching reaction is completed, the obtained colloidal suspension solution is centrifuged and washed several times with anhydrous ethanol, and the pH of the supernatant is tested until the pH value of the supernatant reaches 10. Then ultrasonically treat it for 120 minutes to make it evenly dispersed, and Ti3C2T X The monolayer nanosheet ethanol solution is then vacuum-freeze-dried to obtain Ti3C2T X Single-layer nanosheet powder.
[0082] (2) Ti3C2T X After weighing the nanosheet powder, soak it in a beaker containing silver nitrate aqueous solution, seal it with a laboratory sealing film and let it stand directly to promote the adsorption of silver ions. This process is carried out in a dark environment. Soak for 12 hours to allow Ag to + Fully adsorbed on Ti3C2T X The solution in the beaker was then irradiated with a laboratory UV lamp for 60 minutes to reduce the Ag + In situ Ag generation 0 , Ag 0 Successfully in-situ deposited on Ti3C2T X On nanosheets;
[0083] (3) According to the stoichiometric ratio of each element in the quaternary material, copper acetate, nickel acetate, ferrous chloride and manganese acetate were weighed and immersed in a sodium chloride solution for in-situ oxidation. X The nanocomposite material was added and immersed for 8 h to form a X The sodium ion quaternary cathode material was generated in situ on the nanosheet and AgCl nanoparticles were successfully deposited. The nanosheet was sealed with a laboratory sealing film and left to stand directly. This process also needs to be operated in a dark environment throughout the process. m Cu 1-x-y-z Ni x Fe y Mn z O2 on Ti3C2T X The nanosheets were fully reacted and the solution was exposed to ultraviolet light for 60 minutes to remove some of the residual Ag. + Reduction to elemental Ag 0 Then use anhydrous ethanol to centrifuge and wash to separate. Finally, vacuum freeze-dry to obtain Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X The metal nanocomposite positive electrode material is subjected to a scanning electron microscope test at 5000 times magnification. The results are as follows Figure 5 As shown in the figure, it can be seen that the sample as a whole presents a single crystal structure of sodium battery quaternary positive electrode material, the particle size is less than 5 microns, and they are all distributed in layers. The surface is clean and tidy, and there are fewer residual alkali particles.
[0084] (4) The Na synthesized above m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X The metal nanocomposite positive electrode material, the conductive agent and the binder PVDF were added to the NMP solution in a mass ratio of 8:1:1, and stirred and mixed thoroughly to obtain a uniform slurry. The slurry was then evenly coated on an aluminum foil and placed in a vacuum drying oven and baked at 90°C to obtain a positive electrode sheet.
[0085] (5) Pair the positive electrode sheet in step (4) with the metallic sodium negative electrode, assemble them into a CR2032 button cell in a glove box filled with an inert atmosphere, and test the electrochemical properties of the composite positive electrode material.
[0086] Example 7
[0087] This embodiment provides a novel quaternary Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X The preparation method of metal nanocomposite positive electrode material and sodium ion battery comprises the following steps:
[0088] (1) Prepare a concentrated hydrochloric acid solution of a certain concentration, add lithium fluoride to the above hydrochloric acid solution and stir for 10-20 minutes until the lithium fluoride is completely dissolved, then slowly add Ti3AlC2 to the solution to prevent violent reaction, and continue stirring for a certain period of time after the addition is completed. After the etching reaction is completed, the obtained colloidal suspension solution is centrifuged and washed several times with anhydrous ethanol, and the pH of the supernatant is tested until the pH value of the supernatant reaches 6. Then ultrasonically treat for 60 minutes to make it evenly dispersed, and Ti3C2T X The monolayer nanosheet ethanol solution is then vacuum-freeze-dried to obtain Ti3C2T X Single-layer nanosheet powder.
[0089] (2) Ti3C2T X After weighing the nanosheet powder, soak it in a beaker containing silver nitrate aqueous solution, seal it with laboratory sealing film and let it stand directly to promote the adsorption of silver ions. This process is carried out in a dark environment. Soak for 8 hours to allow Ag to + Fully adsorbed on Ti3C2T X The solution in the beaker was then irradiated with a laboratory UV lamp for 60 minutes to reduce the Ag + In situ Ag generation 0 , Ag 0 Successfully in-situ deposited on Ti3C2T X On nanosheets.
[0090] (3) According to the stoichiometric ratio of each element in the quaternary material, copper acetate, nickel acetate, ferrous chloride and manganese acetate were weighed and immersed in a sodium chloride solution for in-situ oxidation. X The nanocomposite material was added and immersed for 6 hours to form a X The sodium ion quaternary cathode material was generated in situ on the nanosheet and AgCl nanoparticles were successfully deposited. The nanosheet was sealed with a laboratory sealing film and left to stand directly. This process also needs to be operated in a dark environment throughout the process. m Cu 1-x-y-z Ni x Fe y Mn z O2 on Ti3C2TX The nanosheets were fully reacted and the solution was exposed to ultraviolet light for 60 minutes to remove some of the residual Ag. + Reduction to elemental Ag 0 Then use anhydrous ethanol to centrifuge and wash to separate. Finally, vacuum freeze-dry to obtain Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X The metal nanocomposite positive electrode material is subjected to a scanning electron microscope test at 10,000 times magnification. The results are as follows Figure 6 As shown in the figure, it can be seen that the sample as a whole still presents a single crystal morphology of sodium quaternary positive electrode material, with a particle size of 1-5 microns, and a layered distribution, a clean surface, and good morphology. Further X-ray diffraction measurement was performed, and it was obtained Figure 7 As shown in the spectrum, after analysis and comparison, it was found that the diffraction peaks of the obtained samples in the range of 10°-80° all matched well with the PDF standard card of sodium battery quaternary positive electrode materials, and no obvious impurity peaks appeared, which shows that the target product was successfully synthesized.
[0091] (4) The Na synthesized above m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X The metal nanocomposite positive electrode material, the conductive agent and the binder PVDF were added to the NMP solution in a mass ratio of 8:1:1, and stirred and mixed thoroughly to obtain a uniform slurry. The slurry was then evenly coated on an aluminum foil and placed in a vacuum drying oven and baked at 100°C to obtain a positive electrode sheet.
[0092] (5) Pair the positive electrode sheet in step (4) with the metallic sodium negative electrode, assemble them into a CR2032 button cell in a glove box filled with an inert atmosphere, and test the electrochemical properties of the composite positive electrode material.
[0093] Example 8
[0094] This embodiment provides a novel quaternary Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X The preparation method of metal nanocomposite positive electrode material and sodium ion battery comprises the following steps:
[0095] (1) Prepare a concentrated hydrochloric acid solution of a certain concentration, add lithium fluoride to the above hydrochloric acid solution and stir for 10-20 minutes until the lithium fluoride is completely dissolved, then slowly add Ti3AlC2 to the solution to prevent violent reaction, and continue stirring for a certain period of time after the addition is completed. After the etching reaction is completed, the obtained colloidal suspension solution is centrifuged and washed several times with anhydrous ethanol, and the pH of the supernatant is tested until the pH value of the supernatant reaches 6. Then ultrasonically treat for 60 minutes to make it evenly dispersed, and Ti3C2T X Nanosheet ethanol solution, and finally Ti3C2T X Ti3C2T can be obtained by vacuum freeze drying of nano-ethanol solution X Nanosheet powder.
[0096] (2) Ti3C2T X After weighing the nanosheet powder, soak it in a beaker containing silver nitrate aqueous solution, seal it with laboratory sealing film and let it stand directly to promote the adsorption of silver ions. This process is carried out in a dark environment. Soak for 8 hours to allow Ag to + Fully adsorbed on Ti3C2T X The solution in the beaker was then irradiated with a laboratory UV lamp for 60 minutes to reduce the Ag + In situ Ag generation 0 , Ag 0 Successfully in-situ deposited on Ti3C2T X On nanosheets;
[0097] (3) According to the stoichiometric ratio of each element in the quaternary material, copper acetate, nickel acetate, ferrous chloride and manganese acetate were weighed and immersed in a sodium chloride solution for in-situ oxidation. X The nanocomposite materials were added and immersed for 10 h to form a X The sodium ion quaternary cathode material was generated in situ on the nanosheet and AgCl nanoparticles were successfully deposited. The nanosheet was sealed with a laboratory sealing film and left to stand directly. This process also needs to be operated in a dark environment throughout the process. m Cu 1-x-y-z Ni x Fe y Mn z O2 on Ti3C2T X The nanosheets were fully reacted and the solution was exposed to ultraviolet light for 60 minutes to remove some of the residual Ag. + Reduction to elemental Ag 0 Then use anhydrous ethanol to centrifuge and wash to separate. Finally, vacuum freeze-dry to obtain Na m Cu 1-x-y-z Ni x Fey Mn z O2 / Ag@AgCl / Ti3C2T X Metal nanocomposite cathode materials.
[0098] (4) The Na synthesized above m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag@AgCl / Ti3C2T X The metal nanocomposite positive electrode material, the conductive agent and the binder PVDF were added to the NMP solution in a mass ratio of 8:1:1, and stirred and mixed thoroughly to obtain a uniform slurry. The slurry was then evenly coated on an aluminum foil and placed in a vacuum drying oven and baked at 100°C to obtain a positive electrode sheet.
[0099] (5) Pair the positive electrode sheet in step (4) with the metallic sodium negative electrode, assemble them into a CR2032 button cell in a glove box filled with an inert atmosphere, and test the electrochemical properties of the composite positive electrode material.
[0100] Comparative Example 1
[0101] (1) The Ag / Ti3C2T prepared by the above steps X Nano powder and Na m Cu 1-x-y-z Ni x Fe y Mn z The O2 cathode material was synthesized by wet method and then freeze-dried in vacuum to obtain the quaternary Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag / Ti3C2T X The nanopowder, the conductive agent and the binder PVDF are added to the NMP solution in a mass ratio of 8:1:1 and fully stirred to obtain a uniform slurry, and then the slurry is evenly coated on the aluminum foil and placed in a vacuum drying oven and baked at 70-100°C to obtain the positive electrode sheet.
[0102] (2) Pairing the positive electrode sheet in step (1) with a metallic sodium negative electrode, assembling a CR2032 button cell in a glove box filled with an inert atmosphere, and testing the electrochemical properties of the composite positive electrode material.
[0103] Comparative Example 2
[0104] (1) The AgCl / Ti3C2T prepared by the above steps X Nano powder and Na m Cu1-x-y-z Ni x Fe y Mn z The O2 cathode material was synthesized by wet method and then freeze-dried in vacuum to obtain the quaternary Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / AgCl / Ti3C2T X The nanopowder, the conductive agent and the binder PVDF are added to the NMP solution in a mass ratio of 8:1:1 and fully stirred to obtain a uniform slurry, and then the slurry is evenly coated on the aluminum foil and placed in a vacuum drying oven and baked at 70-100°C to obtain the positive electrode sheet.
[0105] (2) Pairing the positive electrode sheet in step (1) with a metallic sodium negative electrode, assembling a CR2032 button cell in a glove box filled with an inert atmosphere, and testing the electrochemical properties of the composite positive electrode material.
[0106] Furthermore, the Na m Cu 1-x-y-z Ni x Fe y Mn z The cycle performance of the button cell assembled with O2 / Ag@AgCl / MXene composite cathode material was evaluated. At the same time, as a comparison, the battery Na assembled with Comparative Example 1 was also tested. m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag / Ti3C2T X And the Na assembled in Comparative Example 2 m Cu 1-x-y-z Ni x Fe y Mn z O2 / AgCl / Ti3C2T X The above performance of the battery is shown in Table 1. At a voltage of 4.2V, Na m Cu 1-x-y-z Ni x Fe y Mn z The 1C discharge capacity and cycle performance of O2 / Ag@AgCl / MXene composite cathode materials are better than those of Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag / Ti3C2T X and
[0107] Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / AgCl / Ti3C2T X Composite cathode material, according to the electrochemical performance test results after 100 cycles, Na m Cu 1-x-y-z Ni x Fe y Mn z The capacity retention rate of O2 / Ag@AgCl / MXene composite cathode materials is greater than 80%, which is significantly better than that of Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / Ag / Ti3C2T X and
[0108] Na m Cu 1-x-y-z Ni x Fe y Mn z O2 / AgCl / Ti3C2T X The positive electrode material shows that the first charge and discharge efficiency, rate discharge performance and cycle performance of the composite positive electrode material prepared in Examples 1-8 are better than those of the composite positive electrode material in Comparative Examples 1-2. The above results show that by m Cu 1-x-y-z Ni x Fe y Mn z After surface modification of O2, including deposition of precious metal Ag, AgCl doping and composite with high conductivity material MXene, its various performances are significantly improved.
[0109] Table 1 - Electrochemical performance test results of Examples 1-8 and Comparative Examples 1-2
[0110]
[0111] It can be seen from Table 1 above that the batteries made of the positive electrode materials prepared in Examples 1-8 have greater discharge capacity and 100 cycle capacity retention rate after 100 cycles than the batteries made of the positive electrode materials in Comparative Examples 1-2. It can be seen that the preparation of the positive electrode materials in the present invention can improve the discharge capacity and cycle stability.
[0112] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or system. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or system including the element.
[0113] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0114] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a composite positive electrode material, characterized in that: The method comprises the following steps: Step 1, adding a preset mass of lithium fluoride into a concentrated hydrochloric acid solution to completely dissolve it, and slowly adding a MXene precursor and stirring it for a preset time to obtain a colloidal suspension solution; Step 2, washing the colloidal suspension solution by centrifugation with anhydrous ethanol, and detecting the pH value of the supernatant until the pH value reaches 5 to 10, and then performing step-by-step ultrasonic treatment and vacuum freeze drying to obtain MXene nanosheet powder; Step 3: Place the MXene nanosheet powder in a silver nitrate aqueous solution and soak it in a dark environment for 2 to 12 hours to allow the Ag + The Ag is fully adsorbed on the MXene nanosheets and then irradiated with UV light for a preset time to make the Ag + In situ Ag generation 0 After irradiation, the Ag / MXene nanocomposite material was obtained by centrifugal washing and separation with anhydrous ethanol and vacuum freeze drying. Step 4: weigh a preset mass of copper source, nickel source, iron source and manganese source, immerse them in a sodium chloride solution, and add the Ag / MXene nanocomposite prepared in step 3, and continue to immerse them in a dark environment for 2 to 12 hours to generate sodium ion quaternary cathode material in situ on the MXene nanosheets and successfully deposit AgCl nanoparticles, and then irradiate with ultraviolet light for a preset time to make the remaining Ag + In situ Ag generation 0 After irradiation, the Na m Cu 1-x-y- z Ni x Fe y Mn z O2 / MXene metal nanocomposite positive electrode material, wherein 0.5≤m≤1.5, 0 <x<0.5,0<y<0.5,0<z<1,0<1-x-y-z<1。 2. The method for preparing a composite positive electrode material according to claim 1, characterized in that: In step 1, the mass volume ratio of lithium fluoride to concentrated hydrochloric acid solution is (1-5) g: (15-100) mL, and the mass fraction of the concentrated hydrochloric acid solution is 34%.
3. The method for preparing a composite positive electrode material according to claim 1, characterized in that: In step 2, MXene nanosheets including Ti3C2T x 、Nb2CT x 、Mo2CT x 、V2CT x 、Ti2CT x 、Ti2NT x 、V4C3T x 、Nb4C3T x 、Ti3CNT x 、Ta4C3T x and TiNbCT x At least one of .
4. The method for preparing a composite positive electrode material according to claim 1, characterized in that: In step 2, the time of the stepwise ultrasonication is 10 to 120 minutes.
5. The method for preparing a composite positive electrode material according to claim 1, characterized in that: In step 3, the concentration of the silver nitrate aqueous solution is 0.1 mol / L, and the mass volume ratio of the MXene nanosheet powder to the silver nitrate aqueous solution is (10-500) mg: (10-50) mL.
6. The method for preparing a composite positive electrode material according to claim 1, characterized in that: In step 4, the copper source includes at least one of copper sulfate, copper chloride, copper nitrate and copper acetate, the nickel source includes at least one of nickel sulfate, nickel chloride, nickel nitrate and nickel acetate, the iron source includes at least one of ferric sulfate and / or ferrous sulfate, ferric chloride and / or ferrous chloride, ferric nitrate and / or ferrous nitrate, ferric citrate and ferric acetate, and the manganese source includes at least one of manganese sulfate, manganese chloride, manganese nitrate and manganese acetate.
7. The method for preparing a composite positive electrode material according to any one of claims 1 to 6, characterized in that: In step 4, the corresponding metal molar ratios of the copper source, nickel source, iron source and manganese source are (0-1):(0-0.5):(0-0.5):(0-1).
8. The method for preparing a composite positive electrode material according to claim 7, characterized in that: The UV light irradiation time in step 3 and step 4 is 60 minutes respectively.
9. A composite positive electrode material, characterized in that: The composite positive electrode material is prepared according to the method for preparing a sodium ion positive electrode material according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: The sodium ion battery includes a positive electrode sheet, which is prepared by adding the composite positive electrode material in claim 9, a conductive agent, and a binder PVDF in a mass ratio of 8:1:1 to an NMP solution and fully stirring and mixing, then evenly coating the composite positive electrode material on an aluminum foil, and finally baking the composite positive electrode sheet in a vacuum drying oven at 70 to 100°C.
Citation Information
Patent Citations
Surface modified battery material, preparation method thereof and battery
CN115548337A
Sodium-ion battery positive electrode composite material and preparation method and application thereof
CN114373917A
MXene material composite nickel-iron-manganese-based positive electrode material and preparation method and application thereof
CN119153640A
Method of manufacturing metal-coated electrode active material, metal-coated electrode active material and electrode
JP2015185276A
KR20200021731A
Cited By
Self-supporting flexible silver-rich electrode and preparation method and application thereof
CN120341293A